Evaluating Bactericidal Effect of the Antibiotics on the European Foulbrood Disease in Honeybees - Varis Tuktarov (Journal of Global Pharma Technology, 2020)
The paper discusses the results of testing the bactericidal and bacteriostatic effect of various concentrations of pefloxacin and enrofloxacin on European foulbrood pathogens in contrast to oxytetracycline. The work presents the therapeutic efficacy of pefloxacin in treating bee colonies affected by European foulbrood disease. The study tested different methods of introducing medicine in the field experiment. European foulbrood disease revealed at the studied apiaries is caused by Melisococcus plutonium, Bacillus alvei, and Enterococcus faecalis; Brevibacillus laterosporus. In Nurimanovsky and Baimaksky districts (Republic of Bashkortostan, Russia), Melisococcus plutonium, which is the primary causative agent of EFB, has not been detected. The minimum bactericidal concentration of pefloxacin is 0.001% for Enterococcus faecalis, while the minimum level for Brevibacillus laterosporus and Bacillus alvei is 0.01%. Oxytetracycline exceeds the index 10fold, and it is 0.01 % for Enterococcus faecalis and 0.1 % for Brevibacillus laterosporus and Bacillus alvei. The minimum bactericidal concentration of pefloxacin is 0.01% for Melisococcus plutonium, which is 100 times lower than the minimum concentration of oxytetracycline (1.0%). High therapeutic efficacy is achieved (93.8...95.9%) in treating bee colonies affected by European foulbrood disease with pefloxacin by adding the antibiotic to the feed syrup (1:1) at a dose of 0.01%. The value is significantly higher than the effect of oxytetracycline applied at a dose of 0.05% (87.4...88.2%).Keywords: Apis mellifera mellifera L, European foulbrood disease, Bactericidal activity, Fluoroquinolones, pefloxacin.